Empathy, compassion, and theory of mind in obsessive‐compulsive disorder. (31st July 2021) - Salazar Kämpf, Maike; Kanske, Philipp; Kleiman, Alexandra; Haberkamp, Anke; Glombiewski, Julia; Exner, Cornelia
Abstract : Objectives: Individuals with obsessive‐compulsive disorder (OCD) often suffer from impairments in social functioning. This study investigates differences in empathy, compassion, and Theory of Mind (ToM) in individuals with OCD as a possible cause for social functioning deficits. Design: Sixty‐four individuals diagnosed with OCD and 62 healthy individuals completed a naturalistic behavioural task (EmpaToM) and a self‐report measure (Interpersonal Reactivity Index, IRI). Methods: Three preregistered repeated measures analyses of variance (ANOVAs). Results: People with OCD exhibited higher empathy levels – namely increased sharing of others' suffering – in the EmpaToM task and reported more distress (IRI) compared with healthy individuals. Furthermore, no differences in compassion (EmpaToM) between both groups emerged, although people with OCD reported more concern for others (IRI) compared with healthy individuals. Concerning the ToM, no group differences were detected, neither in the behavioural task, nor self‐report. Conclusion: By investigating OCD with diverse scientific practices we shed light on the higher levels of empathy exhibited by individuals with OCD, which are relevant for clinical practice and our understanding of OCD symptomatology. Practitioner Points: ● People with obsessive‐compulsive disorder show higher levels of empathy, that is the increased sharing of others' suffering, compared with healthy individuals in both a traditional self‐report and a naturalistic task. ● Regarding compassion, that is caring for others, their self‐reported compassion was higher in people with OCD. ● In Theory of Mind, that is cognitively understanding the situation of another person, no differences have been found neither at self‐report nor in a naturalistic task compared with healthy individuals. ● Independent of traditional interventions, it could prove useful to improve emotion regulation skills so people with OCD learn to cope with empathic distress. Furthermore, it might strengthen the treatment gains and lower dropout rates if the social mind and consequently social relationships become a topic in the treatment and prevention of OCD.